Patient Safety In Intensive Care Unit Siloam Hospitals Manado, Indonesia: An Overview - Nursalim, Adejohn; Tamusa, Fransien Virginia; Lapian, Lady Galatia (Universitas Ahmad Dahlan, 2015)
The intensive care unit (ICU) is a complex and dynamic environment. Mistake does occur, sometimes with severe consequences. The most common errors reported are concerning airway management and invasive lines, tubes and drains. This research comprised of quantitative review methods to overview the implementation of patient safety and ICU. This research used descriptive research design while investigation underwent within the ward for one week. Data extraction process used questionnaire method to involve all staff members within ICU of Siloam Hospitals Manado. Cronbachâs alpha shows result of 0.854, which is higher than r table for n 96. The questionnaire was deemed reliable. Research showed that ICU staffs have good knowledge, attitude, competencies, situation awareness, leadership, communication, teamwork and team leadership as well as decision making related to patient safety. Moreover, ICU staff was burnt-out due to high workload, more than each staff can bear. Further result showed that fire prevention, life saving control, room and equipments, chemicals and dangerous object safety, management of medical equipments, electrical handling, patient safety, storage cupboard usage and medication management all have good policy and procedure. On the other hand, infection control procedure needs to be improved. From this research, it is concluded that ICU Siloam Hospitals Manado has applied patient safety principlesâ well. For further improvements, the management should consider to conduct trainings to staffs regarding patient safety.